Calibrated pressureless impression technique of ocular prosthesis for eviscerated socket: a case report - Henny Kartika; Ariyani; Ricca Chairunnisa; Haslinda Z. Tamin (Indonesian Journal of Prosthodontic, 2022)
Ocular prosthesis for post evisceration socket often has feeble adaptation to the surrounding tissue due to high sensi-tivity. Excessive pressure given by impression technique would lead to irritably intaglio and bulky palpebral contour of the prosthesis. This article describes a modified method of functional impression which made it easier not only to record the tissue bed surface of the defect but also to get the right contour of the palpebral surface at the same time. A 60-year-old male came to Dental Hospital Universitas Sumatera Utara with evisceration defect as a result of traumatic injury 40 years ago. He complained a facial disfigurement that made him formidable with social interacti-on. Pressureless impression combined with calibrated tray was planned for the patient. Light body PVS material was injected into the socket under slight pressure and the conformer made from visible light cure acrylic resin was in position as a tray. Vertical and horizontal lines marked in the conformer calibrate with the facial marking as a gui-dance for 3-D position. The method is intended to get the fast, accurate position offering the patient ocular prosthesis with great comfort as well as to provide facial contours that improve the patient's psychological and physical outlook.